IDENTIFICAÇÃO DE PADRÕES DE EXPRESSÃO EM DOENÇAS GENÉTICAS USANDO UMA REDE DE INTEGRAÇÃO DE VIAS DE MANUTENÇÃO DO GENOMA, ANGIOGÊNESE, HIPÓXIA EVIGILÂNCIA IMUNOLÓGICA - Vieira, Sylvio André Garcia (2016)
The analysis of the biological formations through computer programs has been turning the interpretation of information quicker, more practical, and more reliable. There are a great number of data stored in specialized databases all over the world, that need to be analyzed and interpreted. On the biological databases, there are data obtained from a variety of ways of research in organisms affected by illnesses such as adenoma and carcinoma. There are also data related to the processes of maintenance of the organism in various levels, called pathways. These pathways act in the organism in a different way in every stage, such as in its normality or in the presence of some genetic disease. This study aims at using graphs in order to develop a model of pathway interaction network that incorporate the maintenance of the genome and other activities of the organism conveyed in adenoma and carcinoma of the adrenal cortex, identifying those who are active in the organism in the presence of gene mutation. In order to determine which pathways are modified in the presence of each disease was used a calculus of relative activity of the route associated to the statistical test Z. To visualize the results, graphs were used, whose junctions represent the pathways and whose edges represent the interactions. Through the computer program developed, it was possible to identify the differences that the organism presents in these conditions, allowing the suggestion of employment of this technique to identify modifications that the organism may present when a new nanoencapsulated drug is used.